ANALISIS KEPEMIMPINAN TERHADAP EFISIENSI PENCAPAIAN TUJUAN PERUSAHAAN: STUDI KASUS KETUA DIVISI CSR PT. BUKIT ASAM - Pratama, Yudhistira Anugerah; Putri, Ria Hutami; Nurokhim, Fathur Rhohman; Sikki, Nurhaeni (Jurnal Inspirasi Ilmu Manajemen, 2024)
To achieve efficiency in achieving organizational goals, leaders can apply five dimensions of leadership based on strategic vision, communication, member development, effective division and tasks, and objective work evaluation. This study describes five dimensions of leadership in the CSR Division of Bukit Asam Company. The study used qualitative descriptive methods using interviews and secondary data. The results showed that the head of CSR Division of Bukit Asam Company has implemented five dimensions of leadership, thus having a significant positive impact, both performance and reputation. In this case, the head of CSR Division of Bukit Asam Company needs to maintain and improve its ability to lead in order to achieve the goals of the CSR Division of Bukit Asam Company efficiently.